2011
DOI: 10.1016/j.geoderma.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Geology and climate conditions affect more humus forms than forest canopies at large scale in temperate forests

Abstract: We investigated by linear gradient analysis (RDA) the relationships between forest humus forms (9 humus forms and the Humus Index) and 148 variables describing geology, climate, soil type, geography and the floristic composition of forest canopies, using 3441 plots of the EcoPlant database covering the whole French territory. Among these variables, geology (alkaline vs acidic substrate) and climate (warm/dry vs cold/rainy) were the major determinants of humus forms, scaling mull humus forms from eumull to dysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 104 publications
4
60
0
1
Order By: Relevance
“…However, the threshold for beech was remarkably higher than the one for 303 pine, indicating a higher trophicity need for beech than for pine. 304 The ecogram developed for beech by Rogister (1978) is to a great extent confirmed in our 313 study (Table 2) The assignment of humus characteristics to the system of 9 humus forms proved sometimes 346 imperfect (Ponge et al 2011), resulting that humus thickness indicators can be a good 347 alternative. 348…”
Section: Forest Floor Models 291supporting
confidence: 68%
See 1 more Smart Citation
“…However, the threshold for beech was remarkably higher than the one for 303 pine, indicating a higher trophicity need for beech than for pine. 304 The ecogram developed for beech by Rogister (1978) is to a great extent confirmed in our 313 study (Table 2) The assignment of humus characteristics to the system of 9 humus forms proved sometimes 346 imperfect (Ponge et al 2011), resulting that humus thickness indicators can be a good 347 alternative. 348…”
Section: Forest Floor Models 291supporting
confidence: 68%
“…Humus form was determined according to Jabiol et al (2007) and 175 converted to the humus index of Ponge and Chevalier (2006) with values ranging from 1 176 (eumull) to 8 (mor) (Ponge et al 2011), and was determined as an average of 16 177 measurements in each plot. 178…”
Section: Forest Floor Variables 166mentioning
confidence: 99%
“…The issue of scale may explain these apparent discrepancies. On a regional scale, climate conditions were the controlling factor influencing soil microbial communities (Brockett et al, 2012) and humus forms (Ponge et al, 2011), while at landscape and local scales, differences in soil biogeochemical processes were more directly derived from differences in tree species (Hannam et al, 2004;Grayston and Prescott, 2005). In our study, base cations (Ca, Mg, K) were the only nutrients identified as indicative of specific ecosite groupings (Table 3).…”
Section: Nutrientsmentioning
confidence: 55%
“…T : separation among groups; A: homogeneity within groups; p: probability value. composition on forest floor nutrient concentrations and soil humus type (Lamarche et al, 2004;Ponge et al, 2011). The issue of scale may explain these apparent discrepancies.…”
Section: Nutrientsmentioning
confidence: 99%
“…This concept of a restricted set of ecosystem 'attractors' (as 26 may wonder whether rhizosphere bacterial and fungal communities are able, by themselves or under 23 vegetation control, to change their environment (exemplified by the humus form) in order to make it 24 more favourable to plant/microbial requirements. The best example of such durable action of a 25 rhizosphere micro-organism on the humus form is the ectomycorrhizal fungus Cenococcum 26 and in a study embracing a wide variety of coniferous and deciduous forest stands covering the whole 1 French territory (Ponge et al, 2011). If humus forms are the stable, visible result of interactions 2 between plants, animals and microbes, and the place where most of these interactions take place, it 3 ensures that geology and climate will act more directly on them (as a habitat) than on organisms 4…”
Section: Introduction 17mentioning
confidence: 99%